2022
DOI: 10.9734/afsj/2022/v21i930459
|View full text |Cite
|
Sign up to set email alerts
|

Do Women in Rural South-West Nigeria Become Pregnant with Sub-optimal Haemoglobin Concentrations?

Abstract: Background: Anaemia is a major public health concern worldwide, particularly in developing countries like Nigeria. In a previous study on determinants of prenatal anaemia, we found out that the majority of our respondents had dietary iron intake below the recommended value of 27mg∕day and all of them belonged to low socio-economic class. We opined that many of our respondents could have become pregnant with sub-optimal haemoglobin concentrations. Aim: This study was carried out to evaluate the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…In our earlier study on pregnant women in the rural communities of SW Nigeria, we found out that many of them were anaemic at booking and could have become pregnant with sub-optimal haemoglobin concentrations [9]. This we later confirmed in another study on non-pregnant WRA in the same community where majority of them were also anaemic [10].…”
Section: Introductionmentioning
confidence: 53%
“…In our earlier study on pregnant women in the rural communities of SW Nigeria, we found out that many of them were anaemic at booking and could have become pregnant with sub-optimal haemoglobin concentrations [9]. This we later confirmed in another study on non-pregnant WRA in the same community where majority of them were also anaemic [10].…”
Section: Introductionmentioning
confidence: 53%